Control of Ge1−x−ySixSny layer lattice constant for energy band alignment in Ge1−xSnx/Ge1−x−ySixSny heterostructures. (7th September 2017) - Fukuda, Masahiro; Watanabe, Kazuhiro; Sakashita, Mitsuo; Kurosawa, Masashi; Nakatsuka, Osamu; Zaima, Shigeaki
Abstract: The energy band alignment of Ge1− x Sn x /Ge1− x − y Si x Sn y heterostructures was investigated, and control of the valence band offset at the Ge1− x Sn x /Ge1− x − y Si x Sn y heterointerface was achieved by controlling the Si and Sn contents in the Ge1− x − y Si x Sn y layer. The valence band offset in the Ge0.902 Sn0.098 /Ge0.41 Si0.50 Sn0.09 heterostructure was evaluated to be as high as 330 meV, and its conduction band offset was estimated to be 150 meV by considering the energy bandgap calculated from the theoretical prediction. In addition, the formation of the strain-relaxed Ge1− x − y Si x Sn y layer was examined and the crystalline structure was characterized. The epitaxial growth of a strain-relaxed Ge0.64 Si0.21 Sn0.15 layer with the degree of strain relaxation of 55% was examined using a virtual Ge substrate. Moreover, enhancement of the strain relaxation was demonstrated by post-deposition annealing, where a degree of strain relaxation of 70% was achieved after annealing at 400 °C. These results indicate the possibility for enhancing the indirect-direct crossover with a strained and high-Sn-content Ge1− x Sn x layer on a strain-relaxed Ge1− x − y Si x Sn y layer, realizing preferable carrier confinement by type-I energy band alignment with high conduction and valence band offsets.